Automatic Analysis of Lexical Complexity: Evaluating The Linguistic Performance of The National and International Publication - Martin, Laily; Suraiya, Lucy; Chan, Almaghvirah (Modality Journal: International Journal of Linguistics and Literature, 2023)
This research is a kind of a comparison study that deals with lexical complexity in the Indonesian scholarsâ€™ journal articles. The analysis covers 98 journal articles from the national and international publication using 25 lexical complexity indices. Results of the research showed that the journal articles of international journals have higher mean scores of lexical complexity indices than the national, but significant differences only occurred in the indices for the lexical sophistication and lexical variation, particularly the type-token ratio and verb variation. This may show the performance gap between the two publications from Indonesian academics as to share the lexical characteristic of the international publication surpass the national.Studi komparatif ini membahas lexical complexity dari artikel-artikel jurnal yang dihasilkan para penulis Indonesia. Analisis dilakukan terhadap 98 artikel jurnal terbitan nasional dan internasional dengan memakai 25 indeks lexical complexity. Hasil penelitian memperlihatkan bahwa artikel-artikel jurnal terbitan internasional memiliki rerata indeks lexical complexity lebih tinggi dibanding terbitan nasional, namun perbedaan signifikan hanya terdapat pada indeks-indeks lexical sophistication dan lexical variation, terutama pada rasio type-token dan verb variation. Hal ini bisa jadi merefleksikan adanya performance gap antara kedua kelompok publikasi yang dihasilkan para akademis Indonesia, sekaligus memperlihatkan bahwa karakteristik leksikal dari publikasi internasional lebih tinggi dibanding publikasi nasionalÂ